2021
DOI: 10.4315/jfp-21-113
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Antibacterial Properties of Kefir by Adding Lactobacillus fermentum grx08

Abstract: Kefir is an acidic-alcoholic fermented milk that can provide probiotic benefits such as intestinal microecological balance regulation, antibacterial activity, and anti-inflammatory activity. In this study, Lactobacillus fermentum grx08 isolated from longevous people was used to further improve the health properties of kefir. L. fermentum grx08 and kefir grains obtained from Xinjiang, China were mixed at ratios of 1:1, 5:1 and 25:1 as starters. The 6 Gram-positive and Gram-negative foodborne pathogens were able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Acetonitrile: water (70:30) was used as the mobile phase at a fixed flow rate of 0.8 mL/min. Lactic acid was determined by HPLC as described previously (Lv et al, 2021).…”
Section: Residual Sugar and Lactic Acid Determinationmentioning
confidence: 99%
“…Acetonitrile: water (70:30) was used as the mobile phase at a fixed flow rate of 0.8 mL/min. Lactic acid was determined by HPLC as described previously (Lv et al, 2021).…”
Section: Residual Sugar and Lactic Acid Determinationmentioning
confidence: 99%
“…Fermentation time, acidity, and quality of the fermented milk can be effectively shortened, increased, and improved through addition of L. fermentum grx08. 4 Lactobacillus fermentum BAL-21-ITTG was found to hydrolyze raffinose and stachyose, reduce phytate content, and increase aglycone content in fermented soybean milk. 5 Lactobacillus fermentum KKL1 produces glucoamylase, ⊍-amylase, and phytase, and increases the content of watersoluble vitamins and minerals in fermented rice beverages.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus fermentum is widely used in the fermented food industry as a starter culture to obtain high‐quality fermentation products. Fermentation time, acidity, and quality of the fermented milk can be effectively shortened, increased, and improved through addition of L. fermentum grx08 4 . Lactobacillus fermentum BAL‐21‐ITTG was found to hydrolyze raffinose and stachyose, reduce phytate content, and increase aglycone content in fermented soybean milk 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria, acetic acid bacteria and yeasts are the dominant microorganisms. Kefir can provide probiotic benefits, such as intestinal microecological balance regulation, antibacterial and anti-inflammatory activity [20]. A systematic review by Vieira et al [21] reports that the bioactive compounds more commonly found in kefir were exopolysaccharides, including kefiran, bioactive peptides, and organic acids, especially lactic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors developed synbiotic drinks from milk fermented by kefir grains and supplemented by inulin, quinoa flour, or with the addition of specific probiotic bacteria [20,29,30]. However, most available milk-based kefir products on the market are produced without kefir grains; they use commercial kefir cultures [31].…”
Section: Introductionmentioning
confidence: 99%